Long noncoding RNA SAMMSON promotes papillary thyroid carcinoma progression through p300/Sp1 axis and serves as a novel diagnostic and prognostic biomarker. Issue 2 (3rd September 2019) - Shao, Liang; Sun, Wei; Wang, Zhihong; Dong, Wenwu; Qin, Yuan
Abstract: Accumulating evidence suggests that long noncoding RNA (lncRNA) plays a fundamental role in cancer progression. However, its biological function in papillary thyroid carcinoma (PTC) has not been fully elucidated. Here, we deciphered the essential role of lncRNA SAMMSON in PTC. SAMMSON was identified to be notably upregulated in PTC cells, tissues, and plasma, and could be used as an effective diagnostic and prognostic biomarker for PTC patients. Knockdown of SAMMSON significantly inhibited PTC cell proliferation and invasion in vitro as well as tumorigenicity and metastasis in vivo. Mechanistically, SAMMSON was transcriptionally elevated by oncogenic Sp1, in turn, upregulated SAMMSON was capable of acting as a scaffold to recruit p300 to increase H3K9ac and H3K27ac levels on Sp1 promoter region, leading to transcriptional activation of Sp1, thereby facilitating PTC progression. Taken together, our data demonstrate that SAMMSON is an oncogenic lncRNA and unveil the crucial role of SAMMSON/Sp1 positive feedback loop in tumorigenesis and aggressiveness of PTC.